Candida spp. colonization among intensive care unit patients : preliminary results - Nascimento, Teresa; Inácio, João; Ferreira, Isabel; Diaz, Priscila; Freitas, Paulo; Barroso, Helena (MDPI, 2021)
Candida spp. colonization is recognized as a major risk factor for invasive candidiasis. To assess patient colonization, upon admission and during their stay in intensive care units (ICU), a surveillance study has been conducted since January 2020, in the Lisbon area of Portugal. A total of 219 swab samples were obtained from 113 ICU patients. The yeast identification was conducted by microbiological conventional and molecular methods. Upon admission to the ICU, 27% of patients were already colonized, and 17% became colonized during their ICU stay. Candida albicans was the most isolated species. These results may offer an opportunity for prevention of candidemia.
Communication abstract: Proceedings of the 5th International Congress of CiiEM - Reducing inequalities in Health and Society, held at Egas Moniz’ University Campus in Monte de Caparica, Almada, from June 16th to 18th, 2021.
This is an open access article distributed under the Creative Commons Attribution License which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.
Keywords: Yeasts; Surveillance; Colonization; Identification; Candida spp.